Handling Pandemic in Islamic Literature (Study of The Book "Badzlul Unto Fadhli ath-Thâ'un" by Imam Ibn Hajar al-Asqalani) - Hariyadi, Sugeng; Muflihin, Ahmad (International Journal Ihya' 'Ulum al-Din, 2021)
In the 9th century of hijri., a big scholar in the field of Hadith, Ibn Hajar al-Asqalani has described the guidance of the Shariat in dealing with an pandemic which was packaged in his book "Badzlul Mâ'un fî Fadhli ath-Thâ'un ". This book should be noted through the comparison of the pandemic study between the arguments of the imam with the views of modern scholars, in order to weigh the weight of their respective views. With this comparison, a scientific method of hazanah Islam can be seen in looking at a problematic community that has repeatedly occurred, such as the pandemic COVID-19, as well as connecting the scientific chain and Islamic literature passed down from the Prophet to the next generation, as it is known that the scientific chain known as 'sanad' is part of religion. This research reveals 3 main topics related to pandemic management guidance, namely the validity of syahid status for the dead, the origin of quarantine, and guidance during and after the pandemic.